Exploring MR regression patterns in rectal cancer during neoadjuvant radiochemotherapy with daily T2- and diffusion-weighted MRI - Bostel, Tilman; Dreher, Constantin; Wollschläger, Daniel; Mayer, A.; König, Franz; Bickelhaupt, Sebastian; Schlemmer, Heinz-Peter; Huber, Peter E.; Sterzing, Florian; Bäumer, Philipp; Debus, Jürgen; Nicolay, Nils (Radiation oncology, 2020)
To date, only limited magnetic resonance imaging (MRI) data are available concerning tumor regression during neoadjuvant radiochemotherapy (RCT) of rectal cancer patients, which is a prerequisite for adaptive radiotherapy (RT) concepts. This exploratory study prospectively evaluated daily fractional MRI during neoadjuvant treatment to analyze the predictive value of MR biomarkers for treatment response.